Drying-induced changes in the structure of alkali-activated pastes - Idawati, Ismail; Susan A., Bernal; John L., Provis; Sinin, Hamdan; Jannie S. J., van Deventer (Springer US, 2013)
Drying of cement paste, mortar, or concrete specimens is usually required as a pre-conditioning step prior to the determination of permeability-related properties according to standard testing methods. The reaction process, and consequently the structure, of an alkali-activated slag or slag/fly ash blend geopolymer binder differs from that of Portland cement, and therefore there is little understanding of the effects of conventional drying methods (as applied to Portland cements) on the structure of the geopolymer binders. Here, oven drying (60 C), acetone treatment, and desiccator/vacuum drying are applied to sodium silicateactivated slag and slag/fly ash geopolymer pastes after 40 days of curing. Structural characterization via X-ray diffraction, infrared spectroscopy, thermogravimetry, and nitrogen sorption shows that the acetone treatment best preserves the microstructure of the samples, while oven drying modifies the structure of the binding gels, especially in alkali-activated slag paste where it notably changes the pore structure of the binder. This suggests that the pre-conditioned drying of alkali activation-based materials strongly affects their microstructural properties, providing potentially misleading permeability and durability parameters for these materials when pre-conditioned specimens are used during standardized testing.